Method for producing carboxyl magnetic beads based on industrial solid waste

By preparing carboxylic magnetic beads from industrial solid waste, synthesize iron tetraoxide particles by hydrothermal method and coat them, the problems of high cost and unstable quality in the existing technology are solved, and efficient and environmentally friendly carboxylic magnetic is achieved. Bead production, suitable for biotechnology.

CN119191368APending Publication Date: 2024-12-27SANGON BIOTECH (SHANGHAI) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411335656.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing carboxy magnetic bead preparation technology has problems such as high cost, harsh process conditions and unstable product quality, which limits its wide application in the field of biotechnology.

Method used

Using a method based on industrial solid waste, the solid waste of ferrous sulfate is arranged into a saturated solution, the heavy metal impurities are removed by mixing extractant, and the ferrous tetraoxide particles are synthesized by hydrothermal method, and the hydroxyl and carboxyl group coating are carried out to prepare High-quality carboxylic magnetic beads.

Benefits of technology

It reduces raw material costs, improves product purity and quality, realizes environmentally friendly resource utilization, and is suitable for applications in biomedical and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191368A_ABST
    Figure CN119191368A_ABST
Patent Text Reader

Abstract

The invention provides a method for producing carboxyl magnetic beads based on industrial solid waste, and relates to the technical field of carboxyl magnetic bead preparation, and the method comprises the following steps: preparing a saturated solution from ferrous sulfate solid waste; removing heavy metal impurities in the saturated solution by using a mixed extraction agent through an extraction method to obtain a ferrous ion crude product; synthesizing the ferrous ion crude product through a hydrothermal method to obtain ferroferric oxide particles; carrying out hydroxyl coating treatment on the ferroferric oxide particles to obtain hydroxyl coated particles; and carrying out carboxyl coating treatment on the hydroxyl coated particles to obtain the carboxyl magnetic bead material. Ferroferric oxide is produced by taking ferrous sulfate solid waste as a raw material through a hydrothermal method, then separation is carried out through a magnetic field, the separated ferroferric oxide is modified with a silicon hydroxyl coupling agent, the required iron oxyhydroxide magnetic beads are directly obtained, waste resources are utilized in an environment-friendly mode, the production cost is reduced, and the method is suitable for industrial production. And the great potential of improving the product quality and functionality is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carboxyl magnetic beads preparation, and in particular to a method for producing carboxyl magnetic beads based on industrial solid waste. Background Art

[0002] Magnetic bead technology is a technology widely used in the fields of biomedicine and chemistry, especially superparamagnetic iron oxide carboxyl magnetic beads (MSP-COOH). This type of magnetic beads has the characteristics of superparamagnetism, fast magnetic response, large specific surface area, excellent monodispersity and colloidal stability. Carboxyl magnetic beads are rich in carboxyl functional groups on their surface, and can effectively couple biological molecules such as proteins, nucleic acids and peptides under the action of specific chemical reagents, thus playing an important role in multiple biotechnology fields such as protein purification, immunoassay, and molecular detection.

[0003] Among the existing carboxyl magnetic bead preparation technologies, chemical synthesis and bio-enzyme methods are the mainstream. The chemical synthesis method is usually carried out by directly combining polymers and carboxyl-containing compounds. The process flow of this method is relatively simple and the conditions are highly controllable. Nevertheless, the application of this method is significantly limited by cost and material selection. For example, the chemical synthesis method usually uses expensive ferroferric oxide as the magnetic material. Although the direct coating of ferroferric oxide is simple in technology, the high cost of raw materials limits the wider application of this technology.

[0004] Although there have been patent reports in recent years that use low-cost trivalent iron salts as raw materials to prepare ferroferric oxide and further coat it, the process conditions required for this method are harsh, resulting in significant difficulties in mass production. In addition, the particle size of ferroferric oxide obtained using trivalent iron salts varies greatly and is unevenly distributed, which may lead to unstable performance of magnetic beads in practical applications, thereby affecting the quality and application effect of the final product.

[0005] In summary, although the existing carboxyl magnetic bead preparation technology can meet certain practical application needs, it still has obvious defects. The high cost, harsh process conditions, unstable product quality and other problems in these technologies have seriously limited the wider commercial application and technological development of carboxyl magnetic beads. In response to these problems, future research and technological improvements need to focus on solving the balance between cost-effectiveness and product quality to promote the deeper and wider application of carboxyl magnetic bead technology in the field of biotechnology.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The first purpose of the present invention is to provide a method for producing carboxyl magnetic beads based on industrial solid waste, which has the advantages of clear synthesis route, high product quality and low cost.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides a method for producing carboxyl magnetic beads based on industrial solid waste, comprising:

[0010] S1, taking ferrous sulfate solid waste and preparing it into a saturated solution;

[0011] S2, using a mixed extractant to remove heavy metal impurities in the saturated solution by extraction to obtain a crude ferrous ion product;

[0012] S3, synthesizing the crude ferrous ion product by a hydrothermal method to obtain ferrosoferric oxide particles;

[0013] S4, performing a hydroxyl coating treatment on the ferrosoferric oxide particles to obtain hydroxyl coated particles;

[0014] S5, performing carboxyl coating treatment on the hydroxyl-coated particles to obtain carboxyl magnetic bead materials.

[0015] In an optional implementation, the step S2 includes:

[0016] S21, measuring the heavy metals in the saturated solution and the content of the heavy metals by atomic absorption spectrophotometry as a first detection result;

[0017] S22, mixing the mixed extractant with the saturated solution to perform a first extraction treatment, standing and stratifying to obtain an aqueous phase and an organic phase respectively;

[0018] S23, using the atomic absorption spectrometry to detect the heavy metals separated from the water phase and the content of the heavy metals as a second detection result;

[0019] S24, judging whether the mixed extractant extraction treatment is qualified according to the second test result and the first test result;

[0020] S25, if the extraction process fails, subjecting the organic phase to the first extraction process again;

[0021] S26, if the extraction treatment is qualified, the organic phase is subjected to a second extraction treatment with a potassium hydroxide aqueous solution, and the aqueous phase is separated to obtain the crude ferrous ion product.

[0022] In an optional embodiment, the extraction qualification standard of the mixed extractant includes at least one of the following conditions:

[0023] A. [Mn] ≤ 40ppm;

[0024] B. [Ni] ≤ 20ppm;

[0025] C, [Cu] ≤ 5ppm;

[0026] D. [Co]≤10ppm.

[0027] In an optional embodiment, the first extraction process comprises:

[0028] The mixed extractant and the saturated solution are mixed for at least 30 minutes, and then allowed to stand for not less than 60 minutes to achieve separation of layers.

[0029] In an optional embodiment, the mixed extractant is an extraction solvent prepared from tributyl phosphate and methyl isobutyl ketone and can be repeatedly used.

[0030] In an optional embodiment, the preparation method of the mixed extractant is:

[0031] The mixed extractant is obtained by mixing tributyl phosphate and methyl isobutyl ketone in a ratio of 2:3.

[0032] In an optional implementation, the step S3 includes:

[0033] S31, adding a saturated sodium hydroxide solution dropwise to the aqueous solution of the crude ferrous ion product, and simultaneously introducing air for aeration treatment to obtain a trivalent iron mixed solution;

[0034] S32, subjecting the ferric iron mixed solution to a hydrothermal reaction to obtain the ferroferric oxide particles.

[0035] In an optional implementation, the step S32 includes:

[0036] S321, adding sodium acetate, PEG8000 and ethylene glycol to the trivalent iron mixed solution, and placing the solution in a reaction vessel for hydrothermal reaction;

[0037] S322, after the reaction is completed, the mixture in the reaction container is allowed to stand at room temperature, and suspended particles therein are subjected to solid-liquid separation using a magnetic nylon-iron-boron material to obtain a crude particle product;

[0038] S323, washing the crude particles with ethanol and water in sequence, and drying them to obtain the ferrosoferric oxide particles;

[0039] Preferably, the temperature of the hydrothermal reaction is 200°C to 240°C;

[0040] Preferably, the hydrothermal reaction time is 60 hours to 66 hours;

[0041] Preferably, the standing time at room temperature is 1.5 hours to 2 hours.

[0042] In an optional implementation, the step S4 includes:

[0043] S41, adding the ferrosoferric oxide particles into an ethanol aqueous solution and performing a dispersion treatment;

[0044] S42, adding alkali solution to adjust pH;

[0045] S43, adding tetraethoxysilane solution and performing dispersion treatment;

[0046] S44, using magnetic NdFeB material for solid-liquid separation;

[0047] S45, washing with an ethanol aqueous solution and drying to obtain the hydroxyl-coated particles.

[0048] In an optional embodiment, the alkali solution is an inorganic base or an organic base;

[0049] Preferably, the alkali solution comprises at least one of sodium carbonate solution, sodium bicarbonate solution, sodium hydroxide solution, aqueous ammonia, ethanolamine, diethanolamine, triethylamine, triethylenediamine, pyridine and N-methylmorpholine.

[0050] In an optional implementation, the S5 includes:

[0051] S51, placing the hydroxyl-coated particles into an ethanol aqueous solution for dispersion treatment;

[0052] S52, adding a carboxyl silane coupling agent, mixing, and performing a dispersion treatment;

[0053] S53, using magnetic NdFeB material for solid-liquid separation;

[0054] S54, washing with ethanol aqueous solution and drying to obtain the carboxyl magnetic bead material.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The method provided by the present invention, based on industrial solid waste production of carboxyl magnetic beads has a number of significant advantages, especially in terms of environmental protection and cost-effectiveness. By comprehensively utilizing ferrous sulfate solid waste, the method not only reduces the dependence on high-priced trivalent iron salts, but also effectively converts waste into valuable products, further promoting the resource utilization of industrial waste.

[0057] First, the method uses solid waste ferrous sulfate as a raw material, which is usually generated in industrial production processes but is often underutilized. By converting these waste materials into high-value carboxyl magnetic beads, the present invention not only reduces the cost of raw materials, but also reduces the environmental burden of industrial waste. Compared with the use of expensive trivalent iron salts, the use of solid waste ferrous sulfate significantly reduces production costs.

[0058] Secondly, the heavy metal impurities in the saturated solution of ferrous sulfate were removed by extraction, which improved the purity and quality of the final product. The presence of heavy metal impurities may have a negative impact on the performance of the magnetic beads, such as affecting their magnetism or stability. The use of mixed extractants effectively separated these impurities from ferrous ions, laying a solid foundation for the subsequent production of nanomagnetic beads.

[0059] Next, the present invention synthesizes ferroferric oxide particles by a hydrothermal method, which can effectively control the size and shape of the particles at a relatively low temperature, thereby obtaining a magnetic material with excellent performance. The use of the hydrothermal method further ensures the high quality and consistency of the ferroferric oxide particles, providing a good foundation for the next step of functionalization.

[0060] Finally, the continuous coating of hydroxyl and carboxyl groups not only improves the functionality of the beads, but also increases their applicability in various biomedical applications. The surface functionalization of carboxyl magnetic beads enables them to effectively bind to biomolecules such as proteins and nucleic acids, providing key performance advantages for applications such as protein purification and immunoassay.

[0061] In summary, the method provided by the present invention demonstrates great potential for utilizing waste resources in an environmentally friendly manner, reducing production costs, and improving product quality and functionality, and meets the current high standards for environmental protection and resource recycling in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0063] Figure 1 This is a schematic diagram of the process of producing carboxyl magnetic beads based on industrial solid waste in this application. DETAILED DESCRIPTION

[0064] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0065] refer to Figure 1 In an embodiment of the present application, a method for producing carboxyl magnetic beads based on industrial solid waste is provided, comprising:

[0066] S1, taking ferrous sulfate solid waste and preparing it into a saturated solution;

[0067] S2, using a mixed extractant to remove heavy metal impurities in the saturated solution by extraction to obtain a crude ferrous ion product;

[0068] S3, synthesizing the crude ferrous ion product by a hydrothermal method to obtain ferrosoferric oxide particles;

[0069] S4, performing a hydroxyl coating treatment on the ferrosoferric oxide particles to obtain hydroxyl coated particles;

[0070] S5, performing carboxyl coating treatment on the hydroxyl-coated particles to obtain carboxyl magnetic bead materials.

[0071] Above-mentioned, the ferrous sulfate solid waste mentioned in the present embodiment, mainly refers to the waste containing ferrous sulfate (FeSO) produced in industrial production process.These waste materials can usually be derived from industrial activities such as metal processing, steel manufacturing, electroplating, and wherein ferrous sulfate is commonly used as reducing agent, mordant or as the manufacturing raw material of other chemicals in industry.In these processes, ferrous sulfate may accumulate in solid form, is not fully utilized, and forms industrial byproduct or waste material.

[0072] In the first step, the ferrous sulfate solid waste is configured into a saturated solution, specifically a saturated aqueous solution, the purpose of which is:

[0073] The purpose of configuring the saturated solution is to effectively extract ferrous ions (Fe2+) from solid waste. Ferrous ions are one of the key raw materials required for the preparation of carboxyl magnetic beads, so they must first be dissolved from solid waste for subsequent treatment and reaction.

[0074] After the ferrous sulfate solid waste is dissolved into a solution, impurities such as heavy metals can be more easily removed through various chemical or physical methods. In this process, extraction, precipitation and other means can be used to purify the solution to ensure that a relatively pure ferrous ion solution is obtained, creating conditions for the subsequent preparation of high-quality ferroferric oxide particles.

[0075] Saturated solution can ensure that the concentration of ferrous ions in the solution reaches the maximum, which is beneficial for the subsequent hydrothermal reaction. In the hydrothermal method, the concentration of reactants in the solution directly affects the formation and quality of the product. By controlling the saturation of the solution, the conditions of the synthesis reaction can be more accurately adjusted to obtain the ideal ferrosoferric oxide particles.

[0076] In summary, the purpose of configuring a saturated solution is to effectively extract and utilize the valuable components in ferrous sulfate solid waste and to create optimal conditions for subsequent synthesis and processing steps.

[0077] The present application example demonstrates a method with significant economic and environmental advantages by using solid waste ferrous sulfate as a raw material to prepare carboxyl magnetic beads. This method improves the traditional production process by utilizing industrial byproducts, namely solid waste ferrous sulfate, which not only reduces the dependence on expensive and high-purity trivalent iron salts or high-purity divalent iron, but also effectively reduces production costs and promotes the recycling of resources.

[0078] In the traditional method, it is a common practice to use high-purity iron salts (such as ferric iron or ferrous iron) as raw materials for preparing carboxyl magnetic beads. Although these materials are of high purity and can be directly used in the production process to ensure the quality and consistency of the product, their cost is relatively high. In addition, these materials usually need to be produced through fine chemical processes, further increasing production costs. In the embodiment of the present application, by using ferrous sulfate solid waste, a low-cost industrial byproduct, the cost of raw materials is effectively reduced. This method makes the production of carboxyl magnetic beads a more cost-effective process and increases the economic feasibility of the industry.

[0079] The use of ferrous sulfate solid waste not only helps to reduce costs, but also has significant environmental value. Ferrous sulfate solid waste is usually regarded as waste in industrial production, and its treatment and disposal may cause environmental pollution. Converting these wastes into valuable carboxyl magnetic beads realizes the reuse of waste and reduces the negative impact of industrial waste on the environment. This "waste to treasure" strategy not only improves the efficiency of resource utilization, but also meets the current global demand for sustainable development and environmental protection.

[0080] By extracting iron ions from ferrous sulfate solid waste, and purifying and synthesizing in subsequent steps, the method in the embodiment of the present application can effectively prepare high-quality carboxyl magnetic beads. These magnetic beads have a wide range of applications in the fields of biomedicine, chemical analysis, environmental monitoring, etc. In addition, the promotion of this method can encourage more industrial enterprises to adopt similar waste utilization strategies, promote the development of environmentally friendly technologies, and promote the realization of green chemistry and circular economy.

[0081] In short, the method in the embodiment of the present application not only significantly reduces the production cost by efficiently utilizing industrial solid waste, but also provides an environmentally friendly solution, providing a new economically feasible and environmentally friendly way for the production of carboxyl magnetic beads. The implementation of this method helps to promote the sustainable development of industrial production and provides an innovative idea for dealing with industrial solid waste problems.

[0082] It should be noted that the reason why ferrous sulfate solid waste contains heavy metal impurities is mainly related to its production and use process. Ferrous sulfate is often used in industrial processes such as metal processing, steel manufacturing, and electroplating. These processes may use or generate substances containing heavy metals. These heavy metals may not be completely consumed or separated during the production process, so they accumulate in the generated ferrous sulfate solid waste.

[0083] The heavy metal impurities contained in ferrous sulfate solid waste mainly include manganese (Mn), nickel (Ni), copper (Cu) and cobalt (Co). The presence of these impurities mainly comes from cross-contamination in raw materials or production processes, because these metals are often used in industrial activities such as metal processing, steel manufacturing and electroplating. The following are the potential effects of these heavy metals on the preparation of carboxyl magnetic beads:

[0084] Manganese (Mn): Manganese is a common industrial metal used in steel production and other alloys. The presence of manganese in the preparation of carboxylated magnetic beads may affect the magnetic properties of the final product because manganese can change the crystal structure and magnetic properties of iron oxides.

[0085] Nickel (Ni): Nickel is another metal that is widely used in electroplating and alloy manufacturing. The presence of nickel may interfere with the magnetic response and stability of carboxylated magnetic beads by forming different magnetic phases (e.g., nickel-iron alloys).

[0086] Copper (Cu): Copper is widely used in electrical engineering and electronics and may also be present in carboxyl magnetic beads prepared from ferrous sulfate solid waste. The presence of copper may affect the chemical stability and reactivity of the beads, as copper is a catalytically active metal and may catalyze some unwanted side reactions.

[0087] Cobalt (Co): Cobalt is commonly used to prepare magnetic materials and certain high-performance alloys. In the production process of carboxyl magnetic beads, cobalt impurities may affect the performance of magnetic materials, especially in terms of magnetic properties and thermal stability of the beads.

[0088] In the conventional preparation method, trivalent iron salts with higher price and purity are directly used, or high-purity divalent iron is used, which increases the production cost. In the embodiment of the present application, from the perspective of environmental protection, industrial solid waste is used as raw material, considering that industrial solid waste contains a large amount of heavy metal impurities. It should be noted that the presence of these heavy metal impurities may cause the following problems in the preparation process of carboxyl magnetic beads:

[0089] Impact on purity and reaction efficiency: Heavy metal impurities may undergo unnecessary chemical reactions with other components in the reaction system. These reactions may consume the reaction reagents or change the reaction conditions, reducing the preparation efficiency of carboxyl magnetic beads and the purity of the product.

[0090] Interference with magnetic properties: Some heavy metals such as chromium and nickel may interact with iron and affect the magnetic properties of the final magnetic beads, such as magnetic response speed and stability.

[0091] Biocompatibility and safety issues: Carboxyl magnetic beads are widely used in the biomedical field. If they contain toxic heavy metal impurities, they may be toxic to cells or biological systems, limiting their safety and effectiveness in clinical applications.

[0092] Therefore, in the embodiments of the present application, effectively removing these heavy metal impurities from ferrous sulfate solid waste by extraction using a mixed extractant is crucial to ensuring the quality and application safety of the carboxyl magnetic beads.

[0093] In the embodiment of the present application, a method for producing carboxyl magnetic beads based on industrial solid waste is used to show significant improvements in environmental protection and cost-effectiveness. Using ferrous sulfate solid waste as raw material, this waste material that is usually not fully utilized in industrial production is converted into high-value carboxyl magnetic beads, which significantly reduces the need to rely on high-priced trivalent iron salts, while reducing production costs and the environmental burden of industrial waste. The heavy metal impurities in the saturated solution are effectively removed by extraction, which improves the purity and quality of the product and lays a solid foundation for the production of high-quality magnetic beads. In addition, the ferroferric oxide particles synthesized by the hydrothermal method can effectively control the particle size and shape at a lower temperature, ensuring the excellent performance and consistency of the magnetic material. Continuous hydroxyl and carboxyl coating treatment not only improves the functionality of the magnetic beads, but also enhances its applicability in biomedical applications, such as protein purification and immunoassay.

[0094] In general, the method in this embodiment not only promotes the environmentally friendly utilization of waste resources, but also effectively improves the quality and functionality of the product, and fully meets the current high standards for environmental protection and resource recycling in industrial production.

[0095] Furthermore, the step S2 includes:

[0096] S21, measuring the heavy metals in the saturated solution and the content of the heavy metals by atomic absorption spectrophotometry as a first detection result;

[0097] S22, mixing the mixed extractant with the saturated solution to perform a first extraction treatment, standing and stratifying to obtain an aqueous phase and an organic phase respectively;

[0098] S23, using the atomic absorption spectrometry to detect the heavy metals separated from the water phase and the content of the heavy metals as a second detection result;

[0099] S24, judging whether the mixed extractant extraction treatment is qualified according to the second test result and the first test result;

[0100] S25, if the extraction process fails, subjecting the organic phase to the first extraction process again;

[0101] S26, if the extraction treatment is qualified, the organic phase is subjected to a second extraction treatment with a potassium hydroxide aqueous solution, and the aqueous phase is separated to obtain the crude ferrous ion product.

[0102] Further, the extraction qualification standard of the mixed extractant includes at least one of the following conditions:

[0103] A. [Mn] ≤ 40ppm;

[0104] B. [Ni] ≤ 20ppm;

[0105] C, [Cu] ≤ 5ppm;

[0106] D. [Co]≤10ppm.

[0107] In a preferred embodiment, the extraction qualification standard of the mixed extractant includes the above four conditions ABCD at the same time.

[0108] The above step S21 is to determine the content of heavy metals in the saturated solution of ferrous sulfate solid waste so as to evaluate the effect of subsequent treatment. The saturated solution is analyzed using atomic absorption spectrophotometry (AAS) to detect the heavy metal content therein, thereby obtaining a first test result of the heavy metal content, which provides benchmark data for subsequent extraction treatment.

[0109] As mentioned above, Atomic Absorption Spectroscopy (AAS) is an analytical technique used to determine the content of specific elements in a substance. It quantitatively analyzes the elements in a sample based on the absorption characteristics of atoms to light of a specific wavelength. AAS is a highly accurate analytical method that can accurately determine the content of heavy metals and provide a scientific basis for subsequent processes.

[0110] In the examples of the present application, carboxyl magnetic bead materials are prepared, and the raw materials used are industrial solid waste, i.e., ferrous sulfate solid waste, which contains a large amount of heavy metal impurities. The AAS method is used to track the effect of the extraction treatment. The reason is that AAS is a very sensitive analytical technique that can detect very low concentrations of specific elements. This means that even if the heavy metal content is significantly reduced during the extraction process, AAS can accurately detect it. AAS provides a reliable method to quantitatively analyze the content of specific elements, which is crucial for evaluating the extraction efficiency and determining whether the expected purification level has been achieved. Compared with some other analytical techniques, AAS is relatively simple to operate, easy to implement in the laboratory, and efficiency can be further improved through automation.

[0111] As mentioned above, step S22 removes heavy metal impurities in the saturated solution by extraction. Specifically, a mixed extractant (such as a mixture of tributyl phosphate and methyl isobutyl ketone) is mixed with the saturated solution, and the heavy metals are separated by physical action. After mixing and standing, the solution is separated into an aqueous phase and an organic phase, and the heavy metals are transferred to the organic phase. The extraction method can effectively separate and remove heavy metals and improve the purity of the raw materials.

[0112] Step S23 is to use the atomic absorption spectrometry to detect the heavy metals separated in the water phase and the content of the heavy metals as a second detection result. This step is to verify the effect of the extraction process. Specifically, it is necessary to use AAS again to detect the heavy metal content in the water phase, so as to obtain a second detection result of the heavy metal content, and compare it with the first detection result to evaluate the extraction effect.

[0113] By comparing the test results before and after, the effect of the extraction treatment can be intuitively evaluated.

[0114] The aqueous phase was analyzed using the AAS instrument in the same manner according to the operating procedures.

[0115] Among them, the first test result and the second test result both include the types of heavy metal impurities and the amounts of heavy metal impurities. Among them, the first test result is for the original saturated solution, and the second test result is for the impurity layer separated after a first extraction treatment, that is, the water layer. Therefore, through the first test result and the second test result, the extraction efficiency corresponding to each heavy metal impurity can be calculated, and after a first extraction treatment, the amount of each heavy metal impurity separated can be obtained, and the amount of heavy metal impurities remaining in the original saturated solution can be calculated.

[0116] In step S24, it is used to determine whether the extraction process has achieved the expected purification effect. The first and second test results are compared to determine whether the heavy metal content is significantly reduced. If the heavy metal content is reduced to below the predetermined standard, the extraction process is considered qualified. In this step, a clear standard is provided to determine whether the extraction process is successful or not, and a conclusion can be drawn through data analysis and comparison.

[0117] If the extraction process fails, the organic phase is subjected to the first extraction process again, and the extraction process needs to be repeated. The extraction is repeated until the heavy metal content reaches a predetermined standard to ensure the purity of the raw materials and the quality of subsequent products.

[0118] If the extraction treatment is qualified, the organic phase is back-extracted with potassium hydroxide aqueous solution to separate the aqueous phase. The aqueous phase containing ferrous ions, i.e., crude ferrous ions, is obtained. Through back-extraction, the ferrous ions can be recovered and purified to prepare for the next step of hydrothermal synthesis.

[0119] In the laboratory, this can be accomplished by adding aqueous potassium hydroxide to the organic phase and then performing the separation.

[0120] The whole process is an iterative process, and the results of each step will affect the operation of the subsequent steps. Through this method, ferrous ions can be effectively extracted and purified from industrial solid waste, providing high-quality raw materials for the production of carboxyl magnetic beads.

[0121] Furthermore, the first extraction process comprises:

[0122] The mixed extractant and the saturated solution are mixed for at least 30 minutes, and then allowed to stand for not less than 60 minutes to achieve separation of layers.

[0123] Furthermore, the mixed extractant is an extraction solvent prepared from tributyl phosphate and methyl isobutyl ketone and can be used repeatedly.

[0124] The mixed extractant is a mixed solvent prepared from tributyl phosphate (TBP) and methyl isobutyl ketone (MIBK), namely TM-TRSY, which can be reused.

[0125] Furthermore, the preparation method of the mixed extractant is:

[0126] The mixed extractant is obtained by mixing tributyl phosphate and methyl isobutyl ketone in a ratio of 2:3.

[0127] Furthermore, the step S3 includes:

[0128] S31, adding a saturated sodium hydroxide solution dropwise to the aqueous solution of the crude ferrous ion product, and simultaneously introducing air for aeration treatment to obtain a trivalent iron mixed solution;

[0129] S32, subjecting the ferric iron mixed solution to a hydrothermal reaction to obtain the ferroferric oxide particles.

[0130] The purpose of step S31 is to convert ferrous ions (Fe 2+ ) is oxidized to ferric iron (Fe 3+ ), which is the key step in the synthesis of ferroferric oxide (Fe3O4). Saturated sodium hydroxide solution is gradually added (dropped) to a solution containing ferrous ions to adjust the pH value of the solution and promote the oxidation of ferrous ions. At the same time, air aeration is performed to increase the dissolved oxygen in the solution and accelerate the conversion of ferrous ions to ferric ions, thereby obtaining a mixed solution rich in ferric ions, which is the basis for the subsequent hydrothermal synthesis of ferroferric oxide.

[0131] By controlling the pH and aeration conditions, ferrous ions can be effectively oxidized to ferric ions, providing the necessary chemical precursors for the synthesis of ferrosoferric oxide. Aeration treatment is a simple and cost-effective oxidation method.

[0132] As mentioned above, during the process of adding sodium hydroxide, fresh air is continuously introduced for aeration treatment, in order to remove the high concentration of Fe 2+ Gradually converted to Fe 3+ During this process, the color of the solution first changes from light green to dark green, and then gradually changes to yellow. After the addition of the NaOH solution is completed, aeration can be continued for 4 to 4.5 hours to obtain a brown-yellow mixed solid-liquid solution (ferric iron mixed solution).

[0133] The chemical reaction that occurs in this step is as follows:

[0134] 4Fe 2+ +O2+4H2O→4Fe 3+ +8OH - .

[0135] This reaction is more easily carried out in the presence of sodium hydroxide (NaOH) because sodium hydroxide provides the necessary alkaline environment to promote the reaction of oxygen with ferrous ions.

[0136] The above step S32 is to generate ferroferric oxide nanoparticles by a hydrothermal synthesis method, which is the core material for producing carboxyl magnetic beads. Specifically, a solution containing trivalent iron ions is placed in a high temperature and high pressure reactor, usually kept at a temperature of 200°C to 240°C for a certain time (e.g., 60 to 66 hours). The polymerization and crystallization of trivalent iron ions are promoted by high temperature and high pressure conditions to form ferroferric oxide nanoparticles, thereby successfully synthesizing ferroferric oxide nanoparticles, which have superparamagnetism and are ideal materials for preparing magnetic beads.

[0137] In the above steps, the chemical reactions performed are as follows:

[0138] Fe 3+ +Fe 2+ →O2+Fe3O4.

[0139] Under hydrothermal conditions, ferric and ferrous ions can further react to form ferroferric oxide. This process may occur in a hydrothermal reactor at high temperature and pressure, where the hydrothermal conditions provide the necessary energy and environment to promote this reaction.

[0140] The hydrothermal synthesis method can prepare high-purity and high-crystallinity Fe3O4 nanoparticles at a low cost. The size and morphology of Fe3O4 particles can be controlled by adjusting the conditions of the hydrothermal reaction (such as temperature, time, solvent, etc.).

[0141] Specifically, a high temperature and high pressure resistant reactor can be used to precisely control the reaction conditions. After the reaction is completed, the ferroferric oxide particles can be collected by centrifugation, filtration, etc., and washed and dried to remove impurities.

[0142] Furthermore, the step S32 includes:

[0143] S321, adding sodium acetate, PEG8000 and ethylene glycol to the trivalent iron mixed solution, and placing the solution in a reaction vessel for hydrothermal reaction;

[0144] S322, after the reaction is completed, the mixture in the reaction container is allowed to stand at room temperature, and suspended particles therein are subjected to solid-liquid separation using a magnetic nylon-iron-boron material to obtain a crude particle product;

[0145] S323, washing the crude particles with ethanol and water in sequence, and drying them to obtain the ferrosoferric oxide particles;

[0146] Furthermore, the temperature of the hydrothermal reaction is 200°C to 240°C;

[0147] Furthermore, the hydrothermal reaction time is 60 hours to 66 hours;

[0148] Furthermore, the standing time at room temperature is 1.5 hours to 2 hours.

[0149] The above steps provide specific steps for converting the trivalent iron mixed solution into ferroferric oxide particles in the method for producing carboxyl magnetic beads based on industrial solid waste.

[0150] In step S321, sodium acetate, PEG8000 and ethylene glycol are added to the ferric iron mixed solution, and the solution is placed in a reaction vessel for hydrothermal reaction. This step is a key hydrothermal synthesis step for synthesizing ferroferric oxide, and specific chemical substances are added to promote the formation of ferroferric oxide and control its particle characteristics. The components include the following:

[0151] (1) Sodium acetate: As a chelating agent and dispersant, it helps to evenly distribute iron ions and prevent them from premature aggregation.

[0152] (2) PEG8000: As a dispersant, it reduces particle agglomeration and helps control particle size and morphology.

[0153] (3) Ethylene glycol: As a solvent, it provides a reaction medium and also helps control the reaction kinetics.

[0154] After these substances are mixed with a trivalent iron mixed solution, they are placed in a high-temperature and high-pressure reaction vessel for a hydrothermal reaction.

[0155] The reaction container may be a sealable reaction vessel.

[0156] By precisely controlling the type and amount of chemical additives, the physical and chemical properties of ferroferric oxide particles can be finely controlled. Hydrothermal method is a commonly used method for synthesizing nanomaterials, which can obtain high-quality nanomaterials at a lower cost.

[0157] After the reaction in step S321 is completed, the mixture in the reaction container is allowed to stand at room temperature, and the suspended particles therein are subjected to solid-liquid separation using a magnetic rubidium iron boron material to obtain a crude particle product. This step is to separate the ferroferric oxide particles from the reacted mixture. After the reaction is completed, the mixture is allowed to stand at room temperature for a period of time to promote the sedimentation of the particles. The ferroferric oxide particles are adsorbed by a magnetic material (such as rubidium iron boron) to achieve solid-liquid separation.

[0158] In S323, the crude particles are washed with ethanol and water in sequence, and dried to obtain the ferroferric oxide particles. This step is to remove impurities and residual chemicals on the surface of the ferroferric oxide particles to ensure the purity and quality of the particles. The crude particles are first washed with ethanol to remove organic impurities; then washed with water to remove inorganic salts and other water-soluble impurities; after washing, dried to obtain dry ferroferric oxide particles.

[0159] The washing and drying steps ensure the purity of the FeO particles, which is critical for subsequent applications. The quality of the particles can be further improved by controlling the washing and drying conditions.

[0160] Furthermore, the step S4 includes:

[0161] S41, adding the ferrosoferric oxide particles into an ethanol aqueous solution and performing a dispersion treatment;

[0162] S42, adding alkali solution to adjust pH;

[0163] S43, adding tetraethoxysilane solution and performing dispersion treatment;

[0164] S44, using magnetic NdFeB material for solid-liquid separation;

[0165] S45, washing with an ethanol aqueous solution and drying to obtain the hydroxyl-coated particles.

[0166] The above-mentioned dispersion treatment method can be dispersion treatment by ultrasonic equipment.

[0167] The purpose of adding the ethanol solution is to evenly disperse the ferroferric oxide particles in the solvent, provide sufficient contact area for subsequent chemical reactions, ensure uniform reaction on the particle surface, and improve the coating effect.

[0168] In the above, the pH is adjusted by an alkaline solution to a pH of about 10. The pH value of the solution reaches the alkaline conditions required for the reaction. The reaction conditions are optimized to improve the efficiency and uniformity of the hydroxyl coating. A pH meter can be used for real-time monitoring and alkaline solution can be added for adjustment.

[0169] Tetraethoxysilane (TEOS) is a silicon source reagent used to form a hydroxyl silane layer on the surface of ferroferric oxide particles, forming hydroxyl functional groups on the surface. Under the condition of controlling the pH value, TEOS is added to the solution and the dispersion treatment is continued. Through this step, the surface activity of the particles is enhanced, laying the foundation for the next step of carboxyl coating.

[0170] As above, TEOS was added under continuous stirring.

[0171] TEOS is a silane coupling agent that can form a layer of silanol (Si-OH) groups, i.e., hydroxyl groups, on the surface of ferroferric oxide particles through hydrolysis and condensation reactions. These hydroxyl groups can provide additional reaction sites, laying the foundation for subsequent chemical modification and functionalization. Hydroxyl coating can increase the dispersibility and stability of ferroferric oxide particles in aqueous media and prevent agglomeration between particles, which is crucial for improving the application performance of magnetic beads in biomedicine and other fields. Hydroxyl groups are active chemical groups that can further react with other reagents such as carboxyl silane coupling agents to form functional functional groups such as carboxyl groups. These functional groups can be used for further fixation of biomolecules, such as proteins, enzymes, antibodies, etc. The TEOS coating layer can improve the compatibility of ferroferric oxide particles with organic or biological molecules, which is very important for preparing magnetic composite materials with good biocompatibility. In addition, the presence of hydroxyl groups provides more reactivity to the particles, enabling them to react with various molecules, thereby giving the magnetic beads more functions, such as targeting, catalytic activity, etc.

[0172] Furthermore, the alkali solution is an inorganic alkali or an organic alkali;

[0173] Furthermore, the alkali solution includes at least one of sodium carbonate solution, sodium bicarbonate solution, sodium hydroxide solution, aqueous ammonia, ethanolamine, diethanolamine, triethylamine, triethylenediamine, pyridine and N-methylmorpholine.

[0174] Furthermore, the S5 includes:

[0175] S51, placing the hydroxyl-coated particles into an ethanol aqueous solution for dispersion treatment;

[0176] S52, adding a carboxyl silane coupling agent, mixing, and performing a dispersion treatment;

[0177] S53, using magnetic NdFeB material for solid-liquid separation;

[0178] S54, washing with ethanol aqueous solution and drying to obtain the carboxyl magnetic bead material.

[0179] In the above steps, a carboxyl silane coupling agent is added, mixed, and dispersed. The carboxyl silane coupling agent is used to introduce carboxyl functional groups on the surface of the hydroxyl-coated particles, thereby forming carboxyl functional groups on the surface of the hydroxyl-coated particles. In this step, the carboxyl functional groups are introduced to enhance the chemical activity and function of the particles.

[0180] Through these steps, carboxyl magnetic beads with specific surface functional groups can be efficiently synthesized from industrial waste. These magnetic beads have broad application prospects in biomedicine, catalyst carriers, environmental governance and other fields.

[0181] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0182] Example 1

[0183] In this embodiment, carboxyl magnetic beads were prepared by the following method.

[0184] Experimental methods:

[0185] 1. Synthesis of ferroferric oxide:

[0186] (1) Under room temperature conditions of T≈30°C, 1 L of a saturated solution of 250 g / L ferrous sulfate solid waste was prepared, and the contents of other heavy metals contained therein were detected by atomic absorption spectrophotometry (AAS), and the first test results were as follows:

[0187] [Mn]=1725ppm, [Ni]=448ppm, [Cu]=369ppm, [Co]=187ppm.

[0188] (2) 200 ml of tributyl phosphate (TBP) and 300 ml of methyl isobutyl ketone (MIBK) were mixed to prepare a mixed extractant (TBP / MIBK), and the mixed extractant was mixed with the above-prepared saturated solution and stirred for 30 min. After completion, the mixture was allowed to stand for 60 min before separating the layers.

[0189] The water layer was tested for heavy metal content by AAS, and the second test result was as follows:

[0190] [Mn]=34.8ppm, [Ni]=12.2ppm, [Cu] and [Co] were below the detection limit and were not detected, which met the subsequent production requirements.

[0191] The organic phase was taken and back-extracted with 500 ml of 0.02 M KOH solution to obtain crude ferrous ions. After completion, the mixed extractant TM-TRSY can be reused after filtration and separation.

[0192] (3) Slowly drop 1 L of saturated NaOH solution into the aqueous solution of the crude ferrous ion product, and continuously introduce fresh air to aerate it to obtain a trivalent iron mixed solution; the purpose is to remove the high concentration of Fe 2+ Gradually converted to Fe 3+ During this process, the color of the solution first changes from light green to dark green, and then gradually changes to yellow. After the addition of the NaOH solution is completed, aeration is continued for 4-4.5 hours to obtain a brown-yellow mixed solid-liquid solution, which is a trivalent iron mixed solution.

[0193] (4) The above-mentioned ferric iron mixed solution, 450 g of sodium acetate, 200 g of PEG8000, and 8 L of ethylene glycol were put into a 10 L high temperature and high pressure reactor for reaction.

[0194] After the feeding is completed, the reactor is sealed and the temperature is adjusted to T≈200℃~240℃, and the reaction is carried out at this temperature for 60~66h.

[0195] (5) After the reaction is completed, turn off the heating. When the internal temperature reaches room temperature T≈25°C, start unloading. Let the discharged solid-liquid mixture stand at room temperature for 1.5-2 hours to allow the suspended Fe3O4 particles to settle as much as possible.

[0196] The Fe3O4 particles are then absorbed by a strong magnetic NdFeB material to separate them from the liquid as much as possible.

[0197] Subsequently, the residual PEG8000 and ethylene glycol were washed away with ethanol, and the residual inorganic salts were washed away with water. Finally, the mixture was dried for 6 h under the conditions of T≈115°C and P≈-0.09 MPa to obtain 151.3 g of crude particles with a yield of ≈91.1%.

[0198] 2. Hydroxyl coating:

[0199] (1) All the crude particles prepared above were placed in 5 L of 60% ethanol-water solution (ethanol concentration was 60%), and then ultrasonic equipment was used to uniformly disperse them in the solution.

[0200] (2) Add alkali solution (sodium carbonate solution) to adjust the pH so that the solution pH ≈ 10.

[0201] (3) Add 500 ml of TEOS (tetraethoxysilane) solution and sonicate for 1 hour.

[0202] (4) After the ultrasonic treatment, the nylon-iron-boron was separated into solid and liquid by strong magnetic separation, and washed with 50% ethanol-water solution for 3-4 times, and then dried for 1-1.5 hours under the conditions of T≈30°C and P≈-0.09Mpa to obtain hydroxyl-coated particles with a mass of about 141.9g.

[0203] 3. Carboxyl coating:

[0204] (1) The hydroxyl-coated particles prepared above were placed in 5 L of 50% ethanol-water solution (ethanol concentration was 50%), and then ultrasonic equipment was used to uniformly disperse the particles in the solution.

[0205] (2) Add 400 ml of carboxyl silane coupling agent, followed by ultrasonication for 0.5 h.

[0206] (3) After the ultrasonic treatment, the solid-liquid separation was carried out using strong magnetic nebulium iron boron, and the mixture was washed 3-4 times with a 50% ethanol-water solution, and then dried for 1-1.5 h under the conditions of T≈50°C and P≈-0.09 MPa to obtain the final carboxyl magnetic bead material with a mass of 128.7 g.

[0207] Example 2

[0208] In this embodiment, carboxyl magnetic beads were prepared by the following method.

[0209] Experimental methods:

[0210] It is basically the same as Example 1, except that:

[0211] In step 1 (2), 1 L of 250 g / L saturated ferrous sulfate aqueous solution was mixed with 500 ml of TBP / MIBK mixed extractant (300 ml TBP + 200 ml MIBK) for extraction; the second test result was: [Mn] = 46.7 ppm, [Ni] = 20.5 ppm, [Cu] = 8.8 ppm, which met the quality requirements.

[0212] Step 1 (4) The ferric iron mixed solution, 200 g of sodium acetate, 160 g of PEG8000, and 8 L of ethylene glycol were put into a 10 L high temperature and high pressure reactor for reaction.

[0213] After the feeding was completed, the reactor was sealed, the temperature was adjusted to T≈200°C to 240°C, and the reaction was carried out at this temperature for 60 to 72 hours to obtain 58.3 g of crude particles.

[0214] Example 3

[0215] In this embodiment, carboxyl magnetic beads were prepared by the following method.

[0216] Experimental methods:

[0217] It is basically the same as Example 1, except that:

[0218] In step 1(2), 1 L of the 250 g / L saturated solution was mixed with 1000 ml of TBP / MIBK extractant (400 ml of TBP + 600 ml of MIBK) for extraction;

[0219] The second test result of the water layer after extraction was: [Mn]=21.5ppm, and the rest was not detected, which met the quality requirements.

[0220] Then, 400 g of sodium acetate and 5 L of ethylene glycol were put into a 10 L high temperature and high pressure reactor for reaction at T≈200°C to 240°C for 40-48 hours to obtain 56.7 g of crude particles.

[0221] The hydroxyl groups were coated with 300 ml of TEOS, and the carboxyl groups were further coated with 300 ml of carboxyl silane coupling agent to obtain 49.6 g of carboxyl magnetic beads.

[0222] Example 4

[0223] In this embodiment, carboxyl magnetic beads were prepared by the following method.

[0224] Experimental methods:

[0225] It is basically the same as Example 1, except that:

[0226] 1 L of 250 g / L saturated ferrous sulfate aqueous solution was mixed with 200 ml of TBP / MIBK extractant (80 ml TBP + 120 ml MIBK) for extraction.

[0227] The second test result of the water layer after extraction was: [Mn]=111.2ppm, [Ni]=78.8ppm, [Cu]=72.1ppm, [Co]=16.9ppm, which met the quality requirements.

[0228] Then, 400 g of sodium acetate and 5 L of ethylene glycol were put into a 10 L high temperature and high pressure reactor for reaction at T≈200°C to 240°C for 40-48 hours to obtain 57.0 g of crude particles.

[0229] The hydroxyl groups were coated with 300 ml of TEOS, and the carboxyl groups were further coated with 300 ml of carboxyl silane coupling agent to obtain 50.9 g of carboxyl magnetic beads.

[0230] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for producing carboxyl magnetic beads based on industrial solid waste, characterized in that: include: S1, taking ferrous sulfate solid waste and preparing it into a saturated solution; S2, using a mixed extractant to remove heavy metal impurities in the saturated solution by extraction to obtain a crude ferrous ion product; S3, synthesizing the crude ferrous ion product by a hydrothermal method to obtain ferrosoferric oxide particles; S4, performing a hydroxyl coating treatment on the ferrosoferric oxide particles to obtain hydroxyl coated particles; S5, performing carboxyl coating treatment on the hydroxyl-coated particles to obtain carboxyl magnetic bead materials.

2. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 1, characterized in that The step S2 comprises: S21, measuring the heavy metals in the saturated solution and the content of the heavy metals by atomic absorption spectrophotometry as a first detection result; S22, mixing the mixed extractant with the saturated solution to perform a first extraction treatment, standing and stratifying to obtain an aqueous phase and an organic phase respectively; S23, using the atomic absorption spectrometry to detect the heavy metals separated from the water phase and the content of the heavy metals as a second detection result; S24, judging whether the mixed extractant extraction treatment is qualified according to the second test result and the first test result; S25, if the extraction process fails, subjecting the organic phase to the first extraction process again; S26, if the extraction treatment is qualified, the organic phase is subjected to a second extraction treatment with a potassium hydroxide aqueous solution to separate the aqueous phase therein as the crude ferrous ion product; Preferably, the extraction qualification criteria of the mixed extractant include at least one of the following conditions: A. [Mn] ≤ 40ppm; B. [Ni] ≤ 20ppm; C, [Cu] ≤ 5ppm; D. [Co]≤10ppm.

3. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 2, characterized in that, The first extraction process comprises: The mixed extractant and the saturated solution are mixed for at least 30 minutes, and then allowed to stand for not less than 60 minutes to achieve separation of layers.

4. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 2, characterized in that The mixed extractant is an extraction solvent prepared from tributyl phosphate and methyl isobutyl ketone and can be used repeatedly.

5. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 2, characterized in that: The preparation method of the mixed extractant is: The mixed extractant is obtained by mixing tributyl phosphate and methyl isobutyl ketone in a ratio of 2:

3.

6. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 1, characterized in that: The step S3 comprises: S31, adding a saturated sodium hydroxide solution dropwise to the aqueous solution of the crude ferrous ion product, and simultaneously introducing air for aeration treatment to obtain a trivalent iron mixed solution; S32, subjecting the ferric iron mixed solution to a hydrothermal reaction to obtain the ferroferric oxide particles.

7. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 6, characterized in that: The step S32 comprises: S321, adding sodium acetate, PEG8000 and ethylene glycol to the trivalent iron mixed solution, and placing the solution in a reaction vessel for hydrothermal reaction; S322, after the reaction is completed, the mixture in the reaction container is allowed to stand at room temperature, and suspended particles therein are subjected to solid-liquid separation using a magnetic nylon-iron-boron material to obtain a crude particle product; S323, washing the crude particles with ethanol and water in sequence, and drying them to obtain the ferrosoferric oxide particles; Preferably, the temperature of the hydrothermal reaction is 200°C to 240°C; Preferably, the hydrothermal reaction time is 60 hours to 66 hours; Preferably, the standing time at room temperature is 1.5 hours to 2 hours.

8. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 1, characterized in that: The step S4 comprises: S41, adding the ferrosoferric oxide particles into an ethanol aqueous solution and performing a dispersion treatment; S42, adding alkali solution to adjust pH; S43, adding tetraethoxysilane solution and performing dispersion treatment; S44, using magnetic NdFeB material for solid-liquid separation; S45, washing with an ethanol aqueous solution and drying to obtain the hydroxyl-coated particles.

9. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 8, characterized in that: The alkali solution is an inorganic alkali or an organic alkali; Preferably, the alkali solution comprises at least one of sodium carbonate solution, sodium bicarbonate solution, sodium hydroxide solution, aqueous ammonia, ethanolamine, diethanolamine, triethylamine, triethylenediamine, pyridine and N-methylmorpholine.

10. The method for producing carboxyl magnetic beads based on industrial solid waste as claimed in claim 1, characterized in that: The S5 comprises: S51, placing the hydroxyl-coated particles into an ethanol aqueous solution for dispersion treatment; S52, adding a carboxyl silane coupling agent, mixing, and performing a dispersion treatment; S53, using magnetic NdFeB material for solid-liquid separation; S54, washing with ethanol aqueous solution and drying to obtain the carboxyl magnetic bead material.

Citation Information

Cited By

  • Preparation method of magnetic beads for total nucleic acid extraction of trace cell sample, extraction reagent and extraction method

    CN119746819A

  • Preparation method of magnetic beads for extracting total nucleic acid from trace cell samples, extraction reagent and extraction method

    CN119746819B